KELOMPOK USAHA PENGEMBANGAN PRODUK OLAHAN IKAN GABUS (Ophiocephalus striatus), DI KECAMATAN TEMPE KABUPATEN WAJO - Husniati, Husniati (Lembaga Pengabdian kepada Masyarakat Universitas Muslim Indonesia, 2017)
Catfish is a kind of fish that many found in Tempe lake of Wajo district, it contains a lot ofprotein, so it helps in the growth process of children’s brains, besides catfish extract can functionas healing after surgery. Based on discussions with 2 partners, we can conclude some problemsfaced and the soon to be overcome so that the product can compete with other products, problemscan be described as follows: (1) the use of fish flesh processing tool (shredded fish) so that productquality is better and durable, (2) the problem of product diversification from catfish raw material,(3) training on a simple on-line marketing (creating a Blog) and the manufacture of goodpackaging, (4) the problem of management that is the increasing of ability to manage business andimprovement of accounting and financial administration. Target and outcome expected are: (1) themaking of shredded fish, fish gell more hygiene, tasty and durable, (2) introduce and providespinner, fish mixer that serve to help separate oil from fish flesh so shredded and fish gell be tasty,crunchy and durable without preservatives (3) the products can be brand market in Wajo districtand able to compete in AFTA era, (4) cultivate the spirit of entrepreneurship to all members, (5)introduce a new product that had not yet made by 2 (two) partners such as catfish otak-otak andcatfish gellfish, (6) the transfer of technology in oil separating process of fish flesh and fish fleshmixing with ingredient so that the efficiency and effectiveness of product, (7) increased knowledgeabout good marketing management so intertwined cooperation with retail or merchant, and (8)online marketing through blog “UD RATU SENGKANG SULSEL” as an online marketingmedium. To achieve all targets and outcomes, the team conducted a variety of activities, includessocialization ibM activites, gives latest technology, provides training on making shredded fish,kaki naga and fish nuggets, develop entrepreneurship, and provide guidance on production andmarketing management.